(untitled) (Research, Society and Development, 2021)
Palliative care is used in patients who face illnesses that have no cure and compromise their survival. The moment the disease is discovered in a child patient, the nurse must offer all the monitoring, psychosocial and spiritual support for the child and their families, to offer better living conditions throughout the course of treatment until the departure process, which can take years. The aim of this study was to analyze the clinical nursing practice in palliative care performed in children and adolescents. This study is descriptive research, with a search for articles carried out in digital libraries. It was possible to observe in this study that palliative care has evolved a lot over the centuries and has become a professional practice, performed not only by the nursing team, but by the entire multidisciplinary team. In the last century, patients were isolated in a terminal bed and waited for death, without any relief of signs and symptoms. The current scenario is different and requires professional assistance that considers the pain, possible physical, psychosocial, and spiritual complications of the patient and family. Nurses, together with the multidisciplinary team, must support and offer emotional, psychological, spiritual and pain relief support. Finally, it is noteworthy that every professional who works with patients in the final stage of life must understand that they did their best to ease the pain of the patient and their family.